(untitled) (lectio difficilior, 2013)
This article places olive oil in the anointing accounts (Matthew 26:6-13; Mark 14:3-9; Luke 7:36-50 and John 12:1-8) at the centre of the discussions in order to allow for more justice to all parties involved. That all Gospels pass down an anointing account shows the relevance of the act as well as of the controversies involved. The highly sophisticated vocabulary in these accounts shows how it is rooted in the discussions about the quality of olive oil, its price, its relation to the Land and to the Temple. The questions about tithing of perfumed oil can be taken as starting point for a new reading of the anointing accounts. Whether in the pharisaic household, or in the house of the sisters Martha and Mary, or in the house of Simon the Leper – the olive oil arouses questions of belonging and solidarity, which are found in some accounts of Josephus (Vita, BJ) as well as in debates of the rabbis (Mishna). In the house of a Pharisee, the olive oil seems to qualify as „doubtful“ (Luke 7:37 et seq.), whereas the spike nard in Mark 14:3 and John 12:3 explicitly stems from a “trustworthy source.” This analysis bases on a new understanding of the term pistikos as “trustworthy” according to the tithing rules of a ne’aman instead of translating it with “pure, genuine.”